HUBUNGAN GAYA HIDUP DENGAN TERJADINYA PENYAKIT DIABETES MELITUS DI RSU DAERAH Dr R.M DJOELHAM - Rinawati Tarigan (Jurnal Keperawatan Priority, 2022)
Diabetes was a disease caused by disturbances in the absorption of blood sugar by the body, resulting in high levels in the blood. The International Diabetes Federation (IDF) estimated that there were at least 463 million people aged 20-79 years in the world suffering from DM in 2019. This study aimed to determine the relationship between lifestyle and the occurrence of diabetes mellitus. This research is a type of comparative research with a retrospective study design. This research was conducted at RSU Daerah Dr R.M Djoelham and the time of the study was from Augustus-October 2021. The population in this study were all outpatients at the outpatient clinic as many as 143 people and the size of the sample in this study was 40 people. The sampling technique used non-random sampling by accidental sampling. This study uses primary data and secondary data. The results of this study indicate that there is no relationship between diet, exercise and work with diabetes mellitus where the p-value of diet = 0.490 (> 0.05), the p-value of exercise = 0.744 (> 0.05) and the p-value of work = 0.337 (> 0.05), Based on the results of the study, it can be concluded that there is no relationship between lifestyle and the incidence of diabetes mellitus. It is recommended for respondents to continue to strive to increase knowledge about the application of a healthy lifestyle, increase compliance in carrying out treatment therapy programs, and implement a healthy lifestyle.